2020
DOI: 10.3390/ma13204576
|View full text |Cite
|
Sign up to set email alerts
|

Fast Detection of Heat Accumulation in Powder Bed Fusion Using Computationally Efficient Thermal Models

Abstract: The powder bed fusion (PBF) process is a type of Additive Manufacturing (AM) technique which enables fabrication of highly complex geometries with unprecedented design freedom. However, PBF still suffers from manufacturing constraints which, if overlooked, can cause various types of defects in the final part. One such constraint is the local accumulation of heat which leads to surface defects such as melt ball and dross formation. Moreover, slow cooling rates due to local heat accumulation can adversely affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…However, an important AM limitation, which is not yet explicitly addressed in the context of TO, is that of local overheating or heat accumulation during the manufacturing process. Recent experimental observations and better understanding of AM process physics reveal that overheating is not uniquely associated to overhangs, and dedicated analysis of the local thermal history is needed to characterize overheating (Adam and Zimmer 2014;Ranjan et al 2020). The effect is observed in both polymer and metal manufacturing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an important AM limitation, which is not yet explicitly addressed in the context of TO, is that of local overheating or heat accumulation during the manufacturing process. Recent experimental observations and better understanding of AM process physics reveal that overheating is not uniquely associated to overhangs, and dedicated analysis of the local thermal history is needed to characterize overheating (Adam and Zimmer 2014;Ranjan et al 2020). The effect is observed in both polymer and metal manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…A similar observation was presented by Patel et al (2019), showing dross formation even when acute overhangs were avoided. Finally, Ranjan et al (2020) presented LPBF thermal models and showed that the same degree of overhang can result in different thermal behaviour, depending on the heat evacuation capacity of other features in the vicinity. Hence, the geometrical approach of using a unique critical overhang angle throughout the domain could be insufficient for preventing overheating in some regions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such implementation only considers the current layer time without reflection on the temperature of the substrate. Ranjan et al (2017) investigated another approach to avoid overheating in which a combination of a mathematical formulation and density-based topology optimisation was used to adapt a geometry for thermal hotspot formation (Ranjan et al, 2020). In performance-related industries, such as the aerospace industry, weight is an essential aspect in the design and sizing of components.…”
Section: Introductionmentioning
confidence: 99%
“…A detrimental change of the heat conduction through the part towards the base plate, as well as a significant change of the inter layer time (ILT), can lead to severe heat accumulation of the part or areas of local overheating. This, in turn, results in deviations of the thermal history and eventually affects part quality [5,10,13]. In addition to the geometry, there are many other influencing factors on the thermal history of a L-PBF component.…”
Section: Introductionmentioning
confidence: 99%
“…Figure13. Oxygen concentration in the process chamber during the first 300 min of the short ILT process.…”
mentioning
confidence: 99%